Cytokines Profile in Patients with Acute Myocardial Infarction - Al-Hassan, Ahmed Abdul-Hassan Abbas (Al-Nahrain Journal of Science, 2012)
A total of 30 acute myocardial infarction patients and 30 age and sex-matched healthy controls were enrolled in this study. Patients group showed significant increase in serum levels of IL-1α, IL-2 and IL-6 as compared with controls (p